2004
DOI: 10.1149/1.1630594
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanism of the Vanadium 4+/5+ Redox Reaction in Acidic Solutions

Abstract: Study of the mechanism of the vanadium 4+/5+ redox reaction in acidic solutionsThe mechanism of the vanadium VO 2ϩ /VO 2 ϩ redox couple has been examined in acidic aqueous solutions. A detailed understanding of this chemistry is of interest for improving and optimizing the performance of vanadium redox-flow batteries, a promising electrochemical electricity storage technology. The vanadium 4ϩ/5ϩ redox reactions were studied at a rotating disk graphite electrode and polarization curves were obtained in sulfuric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
169
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 21 publications
15
169
0
Order By: Relevance
“…The actual kinetics are highly complex [14,15] but the work of Shah and coworkers [12,13] has demonstrated that the above mechanism provides a good approximation.…”
Section: Model Assumptions and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The actual kinetics are highly complex [14,15] but the work of Shah and coworkers [12,13] has demonstrated that the above mechanism provides a good approximation.…”
Section: Model Assumptions and Developmentmentioning
confidence: 99%
“…In this paper, the evolution of oxygen in the positive electrode on charge, a known side reaction [15,16] with the effects of operating temperature are also incorporated into the model:…”
Section: Model Assumptions and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the linear region of this curve, the transfer coefficient can be deduced from the slope and the rate constants from the intercept. The Tafel method is well established for simple reaction mechanisms (Bamford & Compton, 1986;Diard et al, 1996), but it becomes much more complicated for complex mechanisms (Gattrell et al, 2004;Wang et al, 2004). When there are significant diffusional or ohmic effects in the electrolyte, or additional electrode reactions, the Tafel plot deviates from linearity (Yeum & Devereux, 1989) and the charge transfer parameters cannot be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The redox flow batteries consist of two electrolytes recycled through bipolar cells from large reservoirs; chemical and electrical energy can be interchanged by reversible electrochemical reactions that take place on the electrodes when the electrolytes are charged or discharged [30][31][32][33][34]. The electrolytes are charged when electrical current is applied between the two electrodes and they are pumped through the reactor, if the electrical energy is needed the reactions are reversed and the energy can be withdrawn from the cell.…”
Section: Introductionmentioning
confidence: 99%